Uso de diferentes niveles de yogurt como suplemento en la alimentación de cerdos en la etapa pre inicial en el recinto El Vergel provincia de Los Ríos - Cano Arias, Leonor María (2023)
The objective of this study was to analyze the effect of using different levels of yogurt as a supplement in the feeding of pigs in the pre-initial stage such as: weight gain, body measurements for length and height of the piglets, presence of diarrhea in the treatments, benefit-cost ratio. The experimental design used was a completely randomized design (DCA), using 27 piglets, divided into 3 treatments, with 3 repetitions and 3 experimental units for each of the repetitions, T0 without adding yogurt, T1 10 ml of yogurt was added. and 20 ml of yogurt was added to T2. Weight gain was taken and recorded weekly individually during the 4 weeks that weaning lasted, likewise for the variables of body measurements for height and length, the statistical analysis was carried out with the InfoStat computer system and the test Tukey's at 5%. The results obtained were the following: weight gain per T0 treatments: 4873.33 grams; T1: 4841.11 grams and T2: 5334.44 grams. In the variable of body measurements by treatments (height), the results were the following: T0: 10.22 cm; T1: 10.22 cm and T2: 9.67 cm. In the variable of body measurements by treatments (length) the results were the following: T0: 23.67 cm, T1: 23.67 cm and T2: 23.33 cm. The benefit-cost relationship was as follows: T0: 37%, T1: 40% and T2: 42%